2018
DOI: 10.1111/eci.12873
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for increased chylomicron remnants in rheumatoid arthritis

Abstract: Rheumatoid arthritis patients have higher levels of apo B48 compared to controls with high CVD risk and healthy controls, with normal levels of triglycerides. This accumulation of atherogenic chylomicron remnants may contribute to the elevated CVD risk in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Cardiovascular morbidity and mortality are high in patients with RA owing to accelerated atherosclerosis [33,34]. Hyperlipidemia is an increasingly interesting cardiovascular risk factor given that postprandial triglycerides are similar to and even better than fasting triglycerides as a predictor of cardiovascular disease, with the practical advantage that the patient is not required to fast [15,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular morbidity and mortality are high in patients with RA owing to accelerated atherosclerosis [33,34]. Hyperlipidemia is an increasingly interesting cardiovascular risk factor given that postprandial triglycerides are similar to and even better than fasting triglycerides as a predictor of cardiovascular disease, with the practical advantage that the patient is not required to fast [15,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this approach, we observed that fasting triglyceride and ApoB48 levels were similar in patients with RA and controls, although postprandial ApoB48 levels were higher. Burggraaf et al [33] showed that patients with RA had higher levels of baseline ApoB48 than controls and that the accumulation of atherogenic chylomicron remnants could contribute to the high risk of cardiovascular disease in these patients. Similarly, the authors did not find differences in triglyceride levels between patients and controls, suggesting that lipolysis of chylomicrons could be normal in patients with RA and that perhaps the abnormality lies in the catabolism of chylomicron remnants in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, postprandial triglyceride levels >220 mg/dL are also considered abnormally high [ 14 ]. Postprandial lipidemia has been shown to be higher in RA patients than healthy controls, and an association between postprandial ApoB48 levels and pathologic carotid intima media thickness (cIMT) has been reported [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In RA, higher ApoB48 values are associated with positive titers of anticyclic citrullinated peptide antibody (ACPA) and rheumatoid factor (RF). In contrast, no association was found between inflammatory activity and the use of disease-modifying drugs, possibly because other inflammatory parameters were not assessed and baseline ApoB48 was measured instead of postprandial ApoB48 [ 16 ]. No factors associated with postprandial hyperlipidemia have been identified in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that ongoing inflammation causes an increased clearance of LDL-cholesterol from the circulation, but not necessarily a decreased risk of CVD [6]. Also, an increase in remnants of the triglyceride transporting protein Apolipoprotein B-48 in patients with RA compared to others with high risk of CVD has been seen [7], suggesting an altered blood lipid metabolism. An increased disease activity and inflammation in RA is associated with an altered blood lipid profile and anti-inflammatory pharmacological therapy reduces these alterations [6].…”
Section: Introductionmentioning
confidence: 99%